Pengembangan Perangkat Pembelajaran dengan Pendekatan Konflik Kognitif untuk Meningkatkan Kemampuan Pemecahan Masalah Momentum dan Impuls Peserta Didik - Ricca Veronica; Gunawan Gunawan; Ahmad Harjono; Jannatin 'Ardhuha (Indonesian, 2020)
This study aims to produce a product in the form of a learning device with a cognitive conflict approach that is feasible on momentum and impulse concepts. This study used the Research and Development (R&D) research method with the research model developed in 4D Models, which consisted of defining, designing, developing, and disseminating stages. The feasibility of the developed learning device is seen from the average result of the calculation of the six expert's assessment scores calculated by the device's validity and reliability. Furthermore, the distribution of response questionnaires was carried out to undergraduate students of physics education, University of Mataram, and students of class XI and XII was majoring in Mathematics and Natural Sciences. The research results based on expert judgment indicate that the results of the development of learning tools have a feasibility value with very valid and reliable criteria on the syllabus, lesson plans, student worksheets, and the developed test instruments. The results of student and student responses show a very good response. It can be concluded that the learning device with the cognitive conflict approach is feasible to proceed to the operational trial phase in learning to improve the students' momentum and impulse problem-solving abilities.